2017
DOI: 10.1038/srep42708
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in the transcriptome of Populus hopeiensis in response to abscisic acid

Abstract: Abscisic acid (ABA) plays a fundamental role in plant response and adaptation to abiotic stresses, such as drought, high salinity and low temperature. Populus hopeiensis exhibits exceptional tolerance to water-deficit environments and is therefore an excellent choice for studying drought tolerance in trees. This study provides a global view of transcriptome dynamics in P. hopeiensis in response to exogenous ABA using Illumina RNA-sequencing. Endogenous ABA content increased and reached a peak at 8 h after ABA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The real-time expression analysis of these transcription factors in response to MeJA and wounding has further identified NAC and bHLH transcription factor showing the better response in comparison with other families such as WRKY and AP2/ERF protein. Similarly, dynamic changes in the expression pattern were observed in different transcription factor families in Populus hopeiensis after ABA treatment [ 41 ]. Also, the transcriptome based tissue-specific expression of transcription factor genes provides important information for understanding the development and transcriptional regulation of the paper mulberry [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The real-time expression analysis of these transcription factors in response to MeJA and wounding has further identified NAC and bHLH transcription factor showing the better response in comparison with other families such as WRKY and AP2/ERF protein. Similarly, dynamic changes in the expression pattern were observed in different transcription factor families in Populus hopeiensis after ABA treatment [ 41 ]. Also, the transcriptome based tissue-specific expression of transcription factor genes provides important information for understanding the development and transcriptional regulation of the paper mulberry [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional responses subsequently dictate large-scale response pathways allocating resources and optimizing plant performance under stress through multiple routes. These include biological pathways regulating abiotic stress responses through the regulation of developmental phytohormones such as IAA, ABA, ethylene, GA, and defense hormones SA and JA (Chen et al, 2017). In this study, we found several genes involved in these hormonal pathways with changes in the expression by at least 2-folds following the stress treatment.…”
Section: Discussionmentioning
confidence: 51%
“…Among them, one ABA receptor and two ABA 8'-hydroxylase genes were speci cally down-regulated in the dedifferentiated tissue of E. camaldulensis. Chen et al, reported that the ABA transcripts peaked at 8h after ABA treatment and then signi cantly decreased at latter time points [33]. Although we lack multiple time points of the callus development, it can be speculated that the down-regulation of ABA genes might be necessary for the callus development of Eucalyptus.…”
Section: Discussionmentioning
confidence: 73%